The duke's assassin: exile and death of Lorenzino de' Medici - Dall'Aglio, Stefano (Yale University Press, 2015)
Part I. The eleven year exile -- Death in Florence -- After the crime -- Mirandola and the apologia -- In the shadow of the crescent -- Between Lyons, Paris and Saintes -- Among the plots of the exiles -- Life in Venice -- Between pope and emperor -- Twilight -- Part II. Anatomy of a murder -- License to kill -- Death plots -- The turncoat killer -- The presumed culprit -- A failed trap -- Death in Venice -- Two men in flight -- The emperor's revenge -- Epilogue